IMPLEMENTASI DIGITALISASI SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SD NEGERI 02 BUMIREJO KECAMATAN ULUJAMI KABUPATEN PEMALANG - Istikomah, Istikomah; Anggraeni, Yuli; Nurkolis, Nurkolis (Dharmas Education Journal (DE_Journal), 2024)
The focus of this research is how the implementation of school digitalization can improve the quality of learning at SD Negeri 02 Bumirejo and its supporting and inhibiting factors.  School digitization includes the use of information and communication technology in the education process, including the use of hardware and software.  This research methodology is descriptive qualitative and uses data collection techniques through observation, interviews and documentation. This methodology involves primary and secondary sources.  The results show that school digitalization has provided positive things to the quality of learning, such as increased motivation of students to learn, easy access to learning materials, and improved skills of both students and teachers. This research also identifies some obstacles, including limited technology infrastructure, lack of training for teachers, and limited internet access for some learners. Schools are expected to improve infrastructure, continuous training for teachers, and learners have adequate access to technology and the internet. Effective implementation of digitalization is expected to improve the quality of learning at SD Negeri 02 Bumirejo, Ulujami Sub-district, Pemalang Regency.